The correlation between ECochG parameters and early auditory behavior after cochlear implantation in children. (2nd July 2016) - Stuermer, Konrad Johannes; Beutner, Dirk; Streicher, Barbara; Foerst, Astrid; Felsch, Moritz; Lang-Roth, Ruth; Walger, Martin
Abstract: Objective : The individual outcome after cochlear implantation in children with auditory synaptopathy/neuropathy (AS/AN) is difficult to predict. A tool for preoperative assessment would be helpful for counseling parents. This study evaluates the outcome after CI in children with AS/AN and with sensorineural hearing loss (SNHL), and correlates it with the preoperative ECochG results in order to find specific parameters of prognostic value. Design : The improvement of auditory behavior after CI was retrospectively assessed using the LittlEARS questionnaire and quantified in a score (LS). This score was correlated with the CAP/SP ratio in the preoperative ECochG. The score was further correlated with the patient's age six months following CI. Study sample: Nine children with AS/AN were compared to nine children with SNHL. Results : Both groups showed a significant improvement in LS following CI. There was a significant positive correlation between the CAP/SP ratio and the improvement in LS in all children. The correlation between age and LS was significantly negative in the SNHL group and positive in the AS/AN group. Conclusion : All children with AS/AN and SNHL benefit to a similar extent from CI. The preoperatively assessed CAP/SP ratio has a prognostic value for the development of auditory behavior following CI.